Drug dose adjustment in patients with renal impairment attending a specialized referral hospital, Northwest Ethiopia - Mequanent Kassa Birarra; Gashaw Binega Mekonnen; Dessalegn Asmelashe Gelayee; Nega Tezera Assimamaw; Zemene Demelash Kifle (Metabolism Open, 2022)
Background: Numerous drugs and their metabolites are removed from the body through the kidney. Improper use of drugs in renal impaired patients may therefore, be harmful and have deleterious effects. Thus, this study was aimed at investigating drug dose adjustment in renal impaired patients attending a specialized hospital. Methods: A prospective cross-sectional study was performed at the medical ward in University of Gondar comprehensive specialized hospital from March to May 2018. During the study period, a total of 2100 patients were admitted to the general medical wards. We located and assessed 210 patient files, of which 189 patient files had complete notes. Based on our inclusion criteria, 105 patients had Crcl of ≥ 59 ml per min per 1.73 m2. Therefore, 84 patients fulfilled our inclusion criteria and were included in the final analysis. The collected data were entered into Epi Info version 7 and exported to the statistical package for the social sciences (SPSS) version 20 for statistical analysis. A chi-square test was applied to test the relationship between renal status and dosage adjustment. P-value ≤ 0.05 was considered as statistical significance. Since the number of co-morbidities and number of drugs prescribed was non-normally distributed using the Shapiro-Wilk test (P < 0.001), the spearman correlation test was used (r = 0.228, p = 0.037). Results: The mean age of study participants was 57 years with 57.1% male and 42.9% female. The highest number of renal impaired patients was in stage three 56(66.7%). The mean creatinine clearance (Crcl) was 41.8 ml/min (IQR 24.8–60.9), and the mean serum creatinine (Scr) value of 2.63 mg/dl (IQR 1.3–3.1). More than two third (76.2%) of the study participants had comorbidities. Eighty-four patients with 257 prescription entries were included in the study. Of which 75 prescription entries need a drug dose adjustment. The overall rate of inappropriate dose adjustment was 42.6% (32/75). Inappropriate dose adjustment was more common with vancomycin (14.3%) and ciprofloxacin (6%). Inappropriate drug dose adjustments were associated with patients having intermediate renal insufficiency (P < 0.002) and co-morbid conditions (P < 0.02). Conclusion: The present study demonstrated that inappropriate dose adjustment was common at University of Gondar comprehensive specialized hospital that needs great attention. Vancomycin and ciprofloxacin were the most frequently identified drugs that were inappropriately adjusted. Intermediate renal insufficiency and co-morbidities were statically significant with inappropriate dose adjustment.